The Perry Initiative's Medical Student Outreach Program Recruits Women Into Orthopaedic Residency. Issue 9 (September 2016) - Lattanza, Lisa L.; Meszaros‐Dearolf, Laurie; O'Connor, Mary I.; Ladd, Amy; Bucha, Amy; Trauth‐Nare, Amy; Buckley, Jenni M.
Abstract: Background: Orthopaedic surgery lags behind other surgical specialties in terms of gender diversity. The percentage of women entering orthopaedic residency persistently remains at 14% despite near equal ratios of women to men in medical school classes. This trend has been attributed to negative perceptions among women medical students of workplace culture and lifestyle in orthopaedics as well as lack of exposure, particularly during medical school when most women decide to enter the field. Since 2012, The Perry Initiative, a nonprofit organization that is focused on recruiting and retaining women in orthopaedics, had conducted extracurricular outreach programs for first‐ and second‐year female medical students to provide exposure and mentoring opportunities specific to orthopaedics. This program, called the Medical Student Outreach Program (MSOP), is ongoing at medical centers nationwide and has reached over 300 medical students in its first 3 program years (2012‐2014). Questions/purposes: (1) What percentage of MSOP participants eventually match into orthopaedic surgery residency? (2) Does MSOP impact participants' perceptions of the orthopaedics profession as well as intellectual interest in the field? Methods: The percentage of program alumnae who matched into orthopaedics was determined by annual followup for our first two cohorts who graduated from medical school. All program participants completed a survey immediately before and after the program that assessed the impact of MSOP on the student's intention to pursue orthopaedics as well as perceptions of the field and intellectual interest in the discipline. Results: The orthopaedic surgery match rate for program participants was 31% in our first graduating class (five of 16 participants in 2015) and 28% in our second class (20 of 72 participants in 2016). Pre/post program comparisons showed that the MSOP influenced students' perceptions of the orthopaedics profession as well as overall intellectual interest in the field. Conclusions: The results of our study suggest that The Perry Initiative's MSOP positively influences women to choose orthopaedic surgery as a profession. The match rate for program alumnae is twice the percentage of females in current orthopaedic residency classes. Given these positive results, MSOP can serve as a model, both in its curricular content and logistic framework, for other diversity initiatives in the field.